Recollections of past days: the autobiography of Patience Loader Rozsa Archer - Archer, Patience Loader, 1827-1921, author; Petree, Sandra Ailey, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2006)
For visitors to the Martin's Cove historic site in Wyoming, Patience Loader has become an icon of the disastrous winter entrapment of the Martin and Willie handcart companies. Her record of those events is important, but there is much else of interest in her autobiography. In fact, it is a bit unusual that someone such as her would have left such an engaging record of her life.
"Reccolections of past days": England, 1827-December 1855 -- On the John J. Boyd, December 1855-February 1856 -- America, February-July 1856 -- Starting Westward, July 3-July 28, 1856 -- On the Plains, July 28-November 30, 1856 -- In the Valley, November 30, 1856-December 1858 -- Camp Floyd, December 1858-July 27, 1861 -- On the Trail to Washington, July 27-November 1861 -- Washington, November 1861-April 1866 -- Back to Utah, April 18-July 21, 1866 -- Back in the Valley, July 21, 1866-1872 -- Afterword -- Appendix 1: James and Amy Britnell Loader Family -- Appendix 2: John and Patience Loader Rozsa Family -- Appendix 3: The Latter-day Saints Millennial Star on Handcart Emigration, December 22, 1855 -- Appendix 4: The Mormon on Handcart Emigration, December 1, 1855 -- Appendix 5: Patience Loader to John Jaques and his reply, The Latter-day Saints Millennial Star, June 14, 1856 -- Appendix 6: Marshall Loader to Amy Britnell Loader, August 6, 1857 -- Appendix 7: Patience Loader Rozsa Archer to Tamar Loader Ricks, November 17, 1914.
Keywords: Mormon women -- United States -- Biography; Mormon women -- England -- Biography; Mormons -- Emigration and immigration; Utah Expedition, 1857-1858; Archer, Patience Loader, 1827-1921